Role of radiotherapy in the management of malignant airway obstruction - Hoon Sik Choi; Bae Kwon Jeong; Hojin Jeong; In Bong Ha; Ki Mun Kang (Thoracic Cancer, 2020)
Background A significant proportion of lung cancer patients suffer from malignant airway obstruction (MAO). Palliative external beam radiotherapy (EBRT) is often used to control the symptoms caused by MAO. In this study, we report the effect of palliative EBRT on lung cancer with MAO and analyze the factors that influence it. Methods This study included 75 patients with MAO in lung cancer who underwent palliative EBRT, between 2009 and 2018 and were analyzed retrospectively. Change of dyspnea, tumor response, and overall survival (OS) were recorded. Univariate and multivariate analyses were performed to determine the prognostic factors for treatment outcomes. Results The median follow‐up duration was 2.5 months, and median OS was 2.3 months. Out of 75 patients, dyspnea was improved in 46 patients (61.3%), and tumor was partially decreased in 39 patients (52%). Symptoms improved in all tumor responding patients. The symptom improvement was significantly affected by radiation dose and time to EBRT. The tumor response was significantly affected by pathology, radiation dose, and time to EBRT. Conclusions Palliative EBRT is an effective and safe treatment option for patients with MAO in lung cancer. In particular, high‐dose irradiation and prompt treatment can improve treatment results. Key points Significant findings of the study In MAO patients, tumor response is an important factor for resolving dyspnea and improving survival rate. In order to increase the tumor response, high‐dose irradiation and prompt treatment after symptoms occur are necessary. What this study adds Our study reported the effects of EBRT and prognostic factors in MAO patients. We emphasize that palliative EBRT is a relatively safe and effective treatment in MAO patients, which is a complement to previous studies.